Theoretical prerequisites for substantiating the parameters of a rotary ripper for interrow potato cultivation - Pervushin Vladimir; Salimzyanov Marat; Ivanov Alexey; Kostin Alexander; Shklyaev Konstantin (E3S Web of Conferences, 2023)
The article is devoted to the study of the process of interaction of the rotary ripper’s working bodies with the soil. The classification of rotary machines and implements according to the energy transmitted to the working body and the location of the rotation axis is outlined. The article notes that the main characteristics of the rotor work body motion are the trajectory type, the magnitude and direction of velocity of its most characteristic point, and in some cases, the magnitude and direction of acceleration. The article presents the results of theoretical research in the field of kinematics of interaction of rotary working tools with the soil. The design of the rotary ripper is presented and the description of the trajectory of its working bodies is made, the value of movement of the scraper plate in the contact area with the soil is established. We analyzed the segment of the path from the beginning of contact with the soil (the beginning of dragging the surface layer of soil) and the end of contact (the end of dragging the surface layer of soil), on the line of which weed combing, loosening and destruction of soil crust occurs.